A Case Series Analysis of Basal Cell Carcinoma (BCC): Not the Deadliest but Certainly the Most Destructive Form of Skin Cancer - Aditya Sharma; Ritika Khanna; Parul Khanna; Rahul Khanna; Seema Khanna (Acta Medica International)
Introduction: Basal cell carcinoma (BCC) is the most commonly prevalent variety of skin cancer worldwide. The primary aim of the study was to see the epidemiological, demographic profile, and different variants of BCC along with the outcomes posttreatment in such patients seen in the tertiary healthcare center at our institute, keeping in mind the rising trends in BCC. Materials and Methods: This is a retrospective analysis of 12 patients in whom facial region-related BCC was surgically excised. The details of each patient, including age, gender, BCC type, location, defect size (cm), type of reconstruction, esthetic outcome, and recurrence, were analyzed. Over the course of 2 years (January 2022–December 2023), a total of 12 individuals were diagnosed with BCC and received treatment. With an average age of 66 years (range: 61–70 years), there were 4 males and 8 females. Results: We evaluated the outcomes in the patients who underwent surgical excision for BCC involving the facial region at the surgery department of our tertiary healthcare centre. All our patients responded well to the surgical procedures, i.e., wide local excision of the tumor, and experienced no problems associated with anesthesia or any other systemic complications. Postoperatively, no hematomas or wound site infections were observed in any of the patients. Our patients were followed up for 18 months. During this period, no patient reported graft or flap loss. No patient experienced a recurrence of the tumor or similar lesions. Functionally, the margin was stable and well-aligned. Conclusion: The diagnosis and characterization of BCC must be based on the clinical, imaging, and histopathology features of the tumor mass in addition to the patient’s characteristics. BCC treatment seeks to achieve the best cosmetic results, especially in critical areas like the face, while minimizing side effects and increasing patient satisfaction. Future research may use the clinical and epidemiological data gathered in this study as a reference.